Aplicación de los ejes transversales curriculares y su influencia en el aprendizaje de los estudiantes de 4to 5to 6to grado de educación general básica de la unidad educativa Manuelita Sáenz de la parroquia Ignacio flores cantón Latacunga en el año lectivo 2015-2016 - Allauca Pallo, Silvia Patricia (2016)
This work was done with the aim of research the influence that curricular transversal axes has within on the learning, at the Basic Educational Unit "Manuelita Saenz” in Ignacio Flores parish, Latacunga Canton, which the independent variable has taken into account according to the transversal axes and as the learning dependent variable, it could be done by taken into account the everyday teaching work from teachers in the classrooms, also the shown students development by the traditional teaching. The field research was done through some interviews and surveys by the use of the questionnaire, which was applied to the Principal, teachers and students, this information was tabulated and performed by circular graphics….